Práctica docente y enseñanza de la historia en la escuela primaria. Una reflexión desde el ámbito rural en el municipio de Tzitzio, Michoacán - Rosiles Bruno, Yesenia (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
History courses in primary school are important because students have a first contact with those historical and cultural processes that drive much of what we are today as individuals and society. Moreover, learning History at elementary school is essential for a proper cognitive development. However, inequities exist in the quality and access to elementary education between urban and rural areas, mainly due to an impoverished socio-economic context surrounding rural (and periurban) schools as compared to urban ones. The objective of this thesis was to evaluate the teaching practice during the sixth grade History course in an elementary school in Tzitzio, a low-income village within the state of Michoacán, and suggest a teaching strategy by means of cartoons or comics. The underlying goal was to explore educational strategies that might help in the process of teaching and learning in these unfavored situations. Tzitzio was chosen for two reasons: because it is a marginalized rural village, and because of previous good working relationships with the school‟s headmaster and sixth grade teacher. Comics as a tool or teaching resource were chosen because: a) they have been reported in the literature as a valid complementary teaching tool that encourages critical and creative thinking in kids, b) do not require extra monetary resources by families of children; and c) do not require active participation by parents. It was concluded from the evaluation that the teaching practice did not encourage students to be thoughtful about historical process. Learning facts by heart lead students to feel unrelated to those historical processes of their country and the world they were studying and reviewing during their History course. It is proposed that the use of comics could function as a bridge or link to a more participatory, reflective and inspiring teaching-learning experience during elementary school.

La importancia de la enseñanza de la Historia en la escuela primaria reside en tener un primer contacto con aquellos procesos que explican cuanto de lo que somos hoy en día, como personas y sociedad, es producto de procesos históricos y culturales. Más aún, el aprendizaje de la Historia en el nivel básico es fundamental para un desarrollo cognitivo integral de los estudiantes. Existen inequidades en cuanto a la calidad y acceso a educación básica entre los ámbitos urbano y rural, debido principalmente al mayor nivel de marginación de las escuelas rurales (y periurbanas), en comparación con las urbanas. El objetivo de la presente tesis fue evaluar la practica docente en la asignatura de Historia en una escuela rural primaria y de alta marginación del municipio de Tzitzio, Michoacán, y presentar una propuesta didáctica a través del recurso de la historieta o “comic”. El fin fue explorar el tipo de parámetros que caracterizan la practica docente en medios rurales marginales y plantear estrategias educativas que coadyuven en el proceso de enseñanza-aprendizaje en estas situaciones. Se escogió́ una escuela en la cabecera municipal de Tzitzio por dos razones fundamentales: porque es una localidad rural de alta marginación, y porque se lograron buenos vínculos de trabajo con el director y el maestro de primaria, con el que se llevó a cabo el trabajo. Se escogió́ el cómic como herramienta o recurso didáctico porque: a) ha sido reportado en la literatura como una herramienta didáctica complementaria válida que estimula el pensamiento crítico y creativo; b) no requiere de recursos monetarios extra por parte de las familias de los niños; y c) no requiere de una participación activa por parte de los padres de familia.
Instituto de Investigaciones Históricas. Facultad de Historia. Maestría en Enseñanza de la Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2014-0317; Estudio; Sociedad; Tzitzio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2525